Microwave imaging for brain stroke detection using Born iterative method. Issue 11 (1st August 2013) - Ireland, David; Bialkowski, Konstanty; Abbosh, Amin
Abstract : Microwave imaging reconstruction is applied to an anatomically realistic, numerical head phantom using the Born iterative method for detection of a haemorrhagic stroke within the brain tissues. A forward model is used to estimate back‐scattered signals which are subsequently used in the image reconstruction process. Image reconstruction using excitation signals at 850 MHz is shown to produce the emulated stroke with a high contrast particular to the estimated conductivity profile.